The Role of Motivation in Improving Work Discipline of Educators at El-Fath Elementary Madrasah in Bandung City - Mia Lisartika; Wahyu Hidayat (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Work motivation is a very important factor in improving work discipline. Work discipline is the result of work motivation. Motivation encourages teaching staff to carry out their duties as well as possible. This research uses descriptive qualitative methods. The research was conducted at Madrasah Ibtidaiyyah El-Fath, Bandung City. Data collection was carried out through observation, interviews and documentation. The resource persons for this research were the head of the madrasah and teaching staff of Madrasah Ibtidaiyyah El-Fath, Bandung City. The research results show that the role of motivation can increase the discipline of teaching staff. This is reflected in the work attitudes shown by teaching staff. Motivated teaching staff will always work with full discipline.